2019
DOI: 10.3892/or.2019.7235
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and DNA methylation regulation of arsenic in mouse bladder tissues and in human urothelial cells

Abstract: According to a report of the International Agency for Research on Cancer, arsenic and inorganic arsenic compounds are classified into Group 1 carcinogens with regard to human health. Epidemiological studies indicate that arsenic is one of the main risk factors for the development of bladder cancer. In the present study, arsenic-altered gene expression in mouse bladder tissues and in human urothelial cells was compared. In the mouse model, sodium arsenite-induced mouse urothelial hyperplasia and intracellular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Recently, researchers have begun to study the function of lncRNAs and have found that lncRNAs can affect cell proliferation, migration, differentiation, apoptosis, and other physiological processes ( Jou et al, 2019 ; Wang et al, 2019 ; Xie et al, 2019 ). In this study, we demonstrated that lncRNA-ENST00000421645 can promote apoptosis in T lymphocytes and inhibit IFN-γ secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have begun to study the function of lncRNAs and have found that lncRNAs can affect cell proliferation, migration, differentiation, apoptosis, and other physiological processes ( Jou et al, 2019 ; Wang et al, 2019 ; Xie et al, 2019 ). In this study, we demonstrated that lncRNA-ENST00000421645 can promote apoptosis in T lymphocytes and inhibit IFN-γ secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sodium arsenite can reduce the human urothelial WIF1 gene expression, increase its DNA methylation level, and promote cancer cells’ migration. The WIF1 gene expression and its DNA methylation can be considered as potential biomarkers for the diagnosis of human BCa ( 131 ).…”
Section: Other Factors Affecting the Prognosis Of Bcamentioning
confidence: 99%
“…WIF1 is considered to be a tumor suppressor gene that inhibits the transcription of downstream oncogenes by blocking the WNT/β-catenin signaling pathway. In our previous study, it was found that after treatment with inorganic arsenic, the normal human urothelial cell line SV-HUC1 showed increased migration, and with the increase of treatment time, the expression of WIF1 mRNA decreased, and the DNA methylation level of WIF1 gene increased significantly [ 18 ]. Glutathione S -transferase Mu 5 (GSTM5) is also a tumor suppressor gene in bladder cancer and its DNA methylation ratio could be a tumor biomarker in our previous study [ 19 ].…”
Section: Introductionmentioning
confidence: 99%